Understanding Hadith of The Prophet: The Image and Variety of Muslims’ Awareness in the Region of Gowa - Tasmin Tangngareng (UIN Sunan Kalijaga Yogyakarta, 2017)
This paper presents an extensive examination about understanding Hadith (the Prophetic Tradition); the image and the range of Muslim society awareness in the region of Gowa. The study focuses on the village of Paccinongang in Gowa regency. Data collection techniques implemented include questionnaires, observation sheets, interview records, and direct observation in the field, and the analysis method applied is that of the qualitative-descriptive analysis. The level of the Muslim society’s knowledge of the Prophet’s Hadith in the village of Paccinongang is relatively low, to the extent that, broadly put, they can barely distinguish between the Qur’an and Hadith. The situation similarly applies in their level of understanding of the Prophet’s Hadith. However, there is a correlation between the level of understanding of Hadith and the level of its implementation. The better one’s awareness is, the higher the level of his implementation. In addition, the interest of the Muslim society in the Village of Paccinongang in studying the Prophet’s Hadith is relatively high. They wish for specific Hadith instructions and assessments in both formal and non-formal conducts. Additionally, the perception of Muslim society in the Village of Paccinongang about the position of the Department of Tafsir Hadith of UIN Alauddin as a learning institution for the Prophet’s Hadith is amazingly positive. The proof is that about 71% of respondents chose formal education as a fitting set for Hadith learnings.[Artikel ini mengkaji secara mendalam tentang pemahaman hadis Nabi saw, yakni potret dan ragam pengetahuan masyarakat Muslim Kabupaten Gowa. Fokus penelitian ini adalah kelurahan paccinongang Kab. Gowa. Tingkat pengetahuan masyarakat muslim kelurahan Paccinongang tentang hadis Nabi tergolong masih rendah kecuali bahwa pada umumnya mereka dapat membedakan al-Qur’an dan Hadis Nabi. Demikian pula tingkat Pemahaman masyarakat Muslim di Kelurahan Paccinongang Kecamatan Somba Opu, Kabupaten Gowa tentang hadis Nabi pada umumnya juga masih rendah. Namun, ada korelasi antara tingkat pemahaman hadis dan tingkat pengamalannya. Semakin tinggi pemahaman seseorang tentang hadis Nabi, maka semakin tinggi pula tingkat pengamalannya. Di samping itu,Minat masyarakat Muslim di Kelurahan Paccinongang, Kecamatan Somba Opu Kabupaten Gowa mempelajari hadis Nabi tergolong tinggi. Mereka menginginkan agar ada pengajian khusus hadis dan pengkajian hadis, baik secara formal maupun non formal. Selain itu, persepsi masyarakat Muslim Kelurahan Paccinongang kecamatan Somba Opu Kabupaten Gowa tentang posisi dan kedudukan Jurusan Tafsir-Hadis UIN Alauddin sebagai institusi pembelajaran hadis Nabi sangat positif. Terbukti bahwa sekitar 71% responden memilih jalur pendidikan formal sebagai tempat belajar hadis.]